2014
DOI: 10.1128/jvi.03460-13
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gammaherpesvirus 68 Encoding Open Reading Frame 11 Targets TANK Binding Kinase 1 To Negatively Regulate the Host Type I Interferon Response

Abstract: Upon viral infection, type I interferons, such as alpha and beta interferon (IFN-␣ and IFN-␤, respectively), are rapidly induced and activate multiple antiviral genes, thereby serving as the first line of host defense. Many DNA and RNA viruses counteract the host interferon system by modulating the production of IFNs. In this study, we report that murine gammaherpesvirus 68 (MHV-68), a double-stranded DNA virus, encodes open reading frame 11 (ORF11), a novel immune modulator, to block IFN-␤ production. ORF11-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 68 publications
(73 reference statements)
0
27
0
Order By: Relevance
“…KSHV ORF59 encodes PF-8, which is essential for virus genome replication (13)(14)(15)25) as an early late protein (26,27). To test whether these PARP-1-interacting proteins may induce PARP-1 downregulation, we transiently overexpressed KSHV RTA (22), ORF49, and PF-8 in HEK293T cells (19). The results showed that endogenous PARP-1 was downregulated in cells transfected with PF-8 but not in cells transfected with RTA or ORF49 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…KSHV ORF59 encodes PF-8, which is essential for virus genome replication (13)(14)(15)25) as an early late protein (26,27). To test whether these PARP-1-interacting proteins may induce PARP-1 downregulation, we transiently overexpressed KSHV RTA (22), ORF49, and PF-8 in HEK293T cells (19). The results showed that endogenous PARP-1 was downregulated in cells transfected with PF-8 but not in cells transfected with RTA or ORF49 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Polyethylenimine (1 mg/ml; Sigma) was used for the transfection of HEK293T cells, as previously described (19). To obtain PF-8-expressing lentiviruses, a FLAG-tagged PF-8-containing lentiviral vector and packaging vector (kind gifts from Seungmin Hwang, The University of Chicago, Chicago, IL, USA) were cotransfected into HEK293T cells.…”
Section: Cells and Viruses Bc-3 And Bcbl-1 Cells (Kshv-positive Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, vIL6 prevents the formation of the ISGF3 complex possibly by blocking Tyk2 phosphorylation [153] while vIRF2 inhibits ISGF3-mediated transcription [212]. In addition, functional screens in of protein-coding genes of KSHV, EBV and MHV-68 have identified a handful of distantly related IFN antagonists [213-216] referred to as dUTPase-related proteins (DURPs), which comprise ORF10, ORF11 and ORF54 [217]. ORF10 was shown to form an inhibitory complex that includes IFNAR subunits, Jak1 and Tyk2, and STAT2 [214].…”
Section: Evasion Of Innate Immune Responsesmentioning
confidence: 99%
“…While the anti-IFN effect of KSHV ORF54 has not been mechanistically characterized, its MHV-68 homologue induces degradation of IFNAR1 [215]. Currently, there is no report regarding KSHV ORF11 and its potential involvement in IFN signaling but it has been shown that the MHV-68 and EBV homologues can antagonize the type I IFN response, albeit via distinct mechanisms [213, 216]. Thus, DURPs appear to be an emerging family of anti-IFN genes analogous to the vIRFs.…”
Section: Evasion Of Innate Immune Responsesmentioning
confidence: 99%